1995
DOI: 10.1073/pnas.92.20.9323
|View full text |Cite
|
Sign up to set email alerts
|

12(S)-hydroxyeicosatetraenoic acid and 13(S)-hydroxyoctadecadienoic acid regulation of protein kinase C-alpha in melanoma cells: role of receptor-mediated hydrolysis of inositol phospholipids.

Abstract: Protein kinase C (PKC) isoenzymes are essential components of cell signaling. In this study, we investigated the regulation of PKC-a in murine B16 amelanotic melanoma (B16a) Inhibitor studies revealed that PKC was involved in basal and 12(S)-HETE-regulated tumor cell and endothelial cell integrin expression (5), adhesion (6, 7), spreading (5), and experimental metastasis (7). However, the involvement of specific PKC isoform(s) and particularly the related mechanism(s) of action for 12(S)-HETE and 13(S)-HODE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
56
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 30 publications
5
56
1
Order By: Relevance
“…In contrast, the stereoisomer 12(R)-HETE, which is not an LO product, did not have these stimulatory effects, indicating specificity for the LO pathway. Although there is evidence in other cell types for a 12(S)-HETE receptor (37,38), it is not clear from this study whether the effects of 12(S)-HETE on Ras-MAPK activation are mediated by a specific receptor. Because 12(S)-HETE did not directly induce oxidant stress in these cells, 2 additional unknown mechanisms for MAPK activation may be operative.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…In contrast, the stereoisomer 12(R)-HETE, which is not an LO product, did not have these stimulatory effects, indicating specificity for the LO pathway. Although there is evidence in other cell types for a 12(S)-HETE receptor (37,38), it is not clear from this study whether the effects of 12(S)-HETE on Ras-MAPK activation are mediated by a specific receptor. Because 12(S)-HETE did not directly induce oxidant stress in these cells, 2 additional unknown mechanisms for MAPK activation may be operative.…”
Section: Discussionmentioning
confidence: 40%
“…Lipoxygenase products can modulate calcium currents in VSMCs (47) and also induce oxidant stress and inflammatory gene expression (48,49). In cancer cells, 12(S)-HETE has been shown to induce multiple signaling events through a potential receptormediated mechanism (37). Our initial unpublished experiments 2 did not support the presence of specific 12(S)-HETE receptors on VSMCs.…”
Section: Discussionmentioning
confidence: 69%
“…As mentioned, previous reports suggest that the effects of 12(S)-HETE on live cells were the result of receptor-mediated stimulation of phospholipase C, the release of DAG and free Ca 2ϩ , and subsequent kinase activation (33,34). Although such a complex pathway may exist in some systems, it is unlikely to function in growth cones.…”
Section: Discussionmentioning
confidence: 97%
“…A number of reports also implicate AA and/or its metabolites in PKC stimulation (27)(28)(29)(30)(31)(32), but they do not provide evidence for a direct mechanism of activation. Instead, some of them suggest kinase activation via intermediate steps such as the intracellular release of DAG and Ca 2ϩ (33,34). Therefore, the issue has remained unclear.…”
mentioning
confidence: 99%
“…Earlier studies have demonstrated that cis-polyunsaturated fatty acids and their metabolites such as HETEs activate PKC isozymes of conventional type (a, b and g isozymes) in several cell types (Liu et al, 1995;Kikkawa et al, 1988;Hansson et al, 1986;McPhail et al, 1984). To understand the mechanism by which arachidonic acid and 12-HpETE induce JNK1 activity, the role of PKC on arachidonic acid and 12-HpETE activation of JNK1 was tested.…”
mentioning
confidence: 99%